Criticism against the Gentlemen Image in England’s Victorian Period in R.L. Stevenson’s The Strange Case of Dr. Jekyll and Mr. Hyde - Vallentina Chelsy; Mala Hernawati (Lexicon, 2018)
England’s Victorian period is marked as an era of historical, technological, economic, and social change. Although science and technological advancement was very progressive—denoted by the Industrial Revolution which took place in this era—the Victorian society’s ideal of moral values, norms, and beliefs was very conservative. Robert Louis Stevenson, a famous Victorian author, wrote The Strange Case of Dr. Jekyll and Mr. Hyde which portrays the complexity of Victorian upper class lives in dealing with the development of science yet facing the strict social norms. This research applies a sociological approach to examine the significant relations between the characterization of the three main characters in the novel—Jekyll, Hyde, and Utterson—and the social issues in the Victorian era. A library research as well as a qualitative method is applied in the process of collecting and analyzing the data. It was found that both Henry Jekyll and Edward Hyde symbolize the repressed individuals of Victorian social norms as Jekyll suppresses his inner-self and separates his dual personality apart in the form of Edward Hyde. As the representation of Jekyll’s evil side, Hyde performs violent and criminal acts which oppose the ideal of social morality. It can be concluded that Jekyll-Hyde’s characterization articulates the social criticism against the firm gentlemen image in the Victorian era. In contrast, Utterson’s characterization represents the epitome of Victorian gentleman.